2012
DOI: 10.1161/strokeaha.111.647263
|View full text |Cite
|
Sign up to set email alerts
|

Silent Intralesional Microhemorrhage as a Risk Factor for Brain Arteriovenous Malformation Rupture

Abstract: Background and Purpose We investigated whether brain arteriovenous malformation (bAVM) silent intralesional microhemorrhage (SIM), i.e., asymptomatic bleeding in the nidal compartment, might serve as a marker for increased risk of symptomatic intracranial hemorrhage (ICH). We evaluated two markers to assess the occurrence of SIM: neuroradiological assessment of evidence of old hemorrhage (EOOH)— imaging evidence of bleeding before the outcome events, and hemosiderin positivity in H&E-stained paraffin block sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 16 publications
(23 reference statements)
2
73
1
Order By: Relevance
“…Consistent with our published data, [21] hemosiderin deposition was found in 8 out of 19 specimens (42%; 95% CI: 20–67%) [Figure 1]. Hemosiderin positive cells were scattered mainly around the abnormal vessels [Figure 1a].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with our published data, [21] hemosiderin deposition was found in 8 out of 19 specimens (42%; 95% CI: 20–67%) [Figure 1]. Hemosiderin positive cells were scattered mainly around the abnormal vessels [Figure 1a].…”
Section: Resultssupporting
confidence: 91%
“…[21] Further, histological examination demonstrated that the degree of hemosiderin deposition is positively correlated with the number of macrophages in the lesion. [21] It is not clear, however, whether the macrophage response is specific or whether other inflammatory cells are also correlated with hemosiderin deposition and macrophage. Our previous studies demonstrated that both macrophage and neutrophil may play roles in bAVM pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Some AVM patients are young with a long life expectancy but they have high-risk features such as silent intralesional hemorrhage, 7 deep location, or deep drainage, all of which increase the risk of future hemorrhage. 5,23,28 For these patients, VS-SRS offers a noninvasive option between resection and observation.…”
Section: Avm Grading and Risk Prediction With Vs-srs Plus Surgerymentioning
confidence: 99%
“…Silent microhemorrhages in unruptured brain AVM patients have been proposed as a novel risk factor for symptomatic hemorrhage [45]. Evidence of old hemorrhage on CT or MR (T1- or T2-weighted sequences) prior to diagnosis but unrelated to any hemorrhage at presentation was present in 6.5% of patients, was highly predictive of hemorrhagic presentation (OR=3.97; 95% CI: 2.1–7.5, P<0.001), and was an independent predictor of new hemorrhage in the natural history course of AVM patients (HR= 3.53, 95% CI=1.35–9.23, P=0.010).…”
Section: Risk Factors For Hemorrhagementioning
confidence: 99%